PENERAPAN PENGHITUNGAN PAJAK DAN PENCATATAN SERTA PELAPORAN PAJAK BUMI DAN BANGUNAN APARTEMEN X - Siahaan, Matdio (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The purpose of this study is about Implementation of Calculation and Recording and Reporting of Land Tax and Building X in Jakarta. The purpose of this study is to know how Land and Building Tax Calculation X, to know the process of Land Tax Listing and Building X Apartment, and to know the form of Land Tax Reporting and Building X Apartment whether it is in accordance with applicable laws and regulations. The method used is qualitative descriptive. The results of this study indicate that the calculations performed in accordance with Governor Regulation No. 77 of 2014, Value of Object Tax (NJOP) in accordance with Governor Regulation No. 263 of 2014 and tariffs in accordance with Regional Regulation No. 16 of 2011. For self-recording bank perception do the recording because Tax payers make payments through bank perception. UPPRD makes two forms of reporting, namely, monthly and annual reporting. Keywords: Pajak Bumi dan Bangunan, Peraturan, Perhitungan, Pencatatan dan Pelaporan